Non-Linear Control of Interleaved Boost Converter Using Disturbance Observer-Based Approach - Avinash Mishra; Sanjoy Mandal; Jean-Yves Dieulot; Mrinal R. Bachute; Mohd Faizan; Anna Pinnarelli; Mehrdad Heidari; Alireza Soleimani (IEEE Access)
Applications such as fuel cell-based electric cars can benefit from the inherent characteristics of interleaved boost converters (IBCs), which include high voltage gain and minimal output voltage and input current ripples. To achieve effective regulation in the face of parameter changes, its critical to maintain the globally stable regulated IBC, especially as the use of highly variable loads increases. An innovative Integral sliding-mode controller along with a disturbance observer for the two-phase IBC (2PIBC) is suggested to ensure such large-signal stability. The time-domain approach is employed to verify the averaged model of the system, which forms basis of designing the controlled system. Several aspects of SMC design are discussed in detail, such as global stability, control signal creation, and sliding surface type selection. The proposed controller is shown to have excellent tracking capabilities with low computations. The use of the recommended control algorithm is demonstrated through MATLAB results and also using experiments based on prototype and using dSPACE 1104.